Prospective Study of Eating Habits as a Predictor of Incident Coronary Heart Disease Hospitalization and Mortality: The 2004 Canadian Community Health Survey. (29th May 2020) - Cahill, Leah; Carew, Allie; Mekary, Rania; Mukamal, Kenneth; Rimm, Eric; Ivey, Kerry; Krikland, Susan; Theou, Olga; Blanchard, Chris; Parkash, Ratika; Urquhart, Robin; Siddiqi, Ferhan; et al.
Abstract: Objectives: Eating habits such as skipping breakfast and snacking are increasingly common practices among North American adults; however, their long-term effects on incident coronary heart disease (CHD) outcomes remain unknown. Previous studies of breakfast skipping and/or eating frequency and cardiometabolic risk have suggested plausible biological pathways for either a protective or harmful relationship to exist, especially when other cardiometabolic risk factors such as diabetes, hypertension, and obesity are present. The objectives of this study were to assess whether long-term associations exist between eating habits (skipping breakfast and eating frequency) and incident CHD (hospitalization and mortality risk), and whether these are intensified by the presence of cardiometabolic risk factors. Methods: Skipping breakfast (yes/no) and eating frequency (times per day) were assessed via a 24-hour dietary recall in a nationally representative sample of 13, 587 adults (aged ≥18 years) in the 2004 Canadian Community Health Survey (CCHS), who were free of CHD and cancer. Data from the CCHS 2.2 were linked to the population-based Discharge Abstract Database and Canadian Mortality Database to determine the incidence of CHD hospitalization and mortality in the subsequent 9 years. Multivariable Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI). Results: During follow-up, 762 cases of CHD hospitalization and mortality were documented. Skipping breakfast was not associated with risk of CHD hospitalization and mortality in all participants together (multivariable-adjusted HR = 1.02, 95% CI: 0.74–1.39) or within baseline risk factor subgroups (hypertension: n = 2472; 0.95, 0.55–1.64; diabetes: n = 826; 1.38, 0.65–2.93; BMI ≥ 30 kg/m 2 : n = 2942; 1.43, 0.84–2.43). Similarly, no associations were observed between eating frequency and risk of CHD hospitalization and mortality. Conclusions: Skipping breakfast and eating frequency were not associated with either increased or decreased risk of CHD hospitalization and mortality in this cohort of Canadian adults. Funding Sources: Nova Scotia Health Research Foundation Development and Innovative Grant and a Nova Scotia Health Authority Research Foundation New Investigator Grant to LEC.